Sufi Ethics for the Digital Age: Developing Virtual Awareness, Moral Conduct, and Self-Control in Online Engagement - Rosyad, Aftonur (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
Technology has become an inseparable part of human life, exerting a significant influence on patterns of living and social behavior. Social media often gives rise to various ethical and moral concerns, including a decline in self-awareness, weakened self-control, and erosion of moral values. Sufism and technology can be integrated to maintain a balance between digital advancement and the spiritual depth of human beings. This article examines the implementation of Sufi teachings in the digital era, focusing on three key aspects: the development of virtual awareness, ethical conduct in digital engagement, and the cultivation of self-control. The study employs a literature-based approach, utilizing descriptive-analytical analysis and drawing on primary and secondary sources, including classical Sufi texts, contemporary literature on digital ethics, and scholarly articles. Its epistemological position is prescriptive, as it not only describes ethical phenomena in the digital sphere but also formulates normative principles based on Sufi teachings to reinforce digital ethics.The findings indicate that Sufism offers a value-based foundation for addressing digital challenges. Virtual awareness can be cultivated through the practices of dhikr, muhasabah, and muraqabah, which position technology as a medium for drawing closer to God. Digital ethics from a Sufi perspective emphasizes the importance of politeness, honesty, and a focus on the public good in every online interaction. Meanwhile, self-control can be exercised through disciplined use of technology, avoidance of negative content, and restraint from excessive digital desires. The implementation of Sufism in the digital era can serve as an effective strategy for maintaining equilibrium between technological utilization and spiritual needs, while simultaneously contributing to the development of a morally refined society.